Legal and Economic Protection of Returning Migrant Workers in Indonesia: A Transcendental Justice Perspective - Ratu Sa'bani; Yulias Erwin; Nurjannah Septyanun (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
The objective of this study is to examine how legal protection policies and economic rights for returned Indonesian migrant workers are formulated and implemented in Indonesia. This research employs a normative legal approach framed by the concept of transcendental justice an approach that goes beyond formal legal analysis to include moral, spiritual, and humanitarian values in assessing and shaping policies. The findings reveal two key conclusions. First, the protection of Indonesian migrant workers after placement is a state responsibility that must be implemented comprehensively and sustainably, covering legal, social, and economic dimensions. Such protection should not be limited to formal regulations but must be translated into real actions such as reintegration programs, skills training, access to business capital, and the active involvement of both central and local governments and related institutions to ensure the well-being and economic independence of returning migrant workers. Second, the current implementation of legal and economic protections remains ineffective. Although regulations like Law No. 18/2017 exist, their enforcement is weak, uneven, and poorly targeted. Many returning workers lack proper support, meaningful training, social security access, and economic recovery. These shortcomings rooted in poor inter-agency coordination and weak accountability indicate that existing protections fall short of realizing true, dignity-based, and holistic justice.